The Influence of Work Safety, Work Motivation, and Work Discipline on Employee Performance at PT Sawit Sukses Sejati - Zebua, Yanti Sepitri; Fitriano, Andre; Yunita, Mella (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study aims to test and analyze the influence of Safety, Motivation, and Work Discipline on Employee Performance at PT. Sawit Sukses Sejati. The method used is a survey technique and filling out a questionnaire on all employees of PT. Sawit Sukses Sejati. The number of samples in this study was 74 employees. The results of the analysis of the hypothesis of this study are t count more than t table which is 5.256 less than 1.967 and the significance value is 0.001 less than 0.005, the value of t count more than t table or 4.02 more than 1.967 and the significance value is 0.001 less than 0.005, the value of t count more than t table or 3.538 more than 1.967 and the significance value is 0.001 less than 0.005. So it can be interpreted that the three independent variables affect the dependent variable. This means that safety, motivation, and work discipline affect the performance of an employee.